PENGEMBANGAN DAN PEMASARAN PRODUK KRIPIK PISANG (BANANA CHIPS) ARSA JAYA KHAS GUNUNG SARI - Ujang Hibar; Budi Susanto; Andi Muhammad Fatur; Sela Febiola; Angga Diwa Permana; Gina Oktaviana; Nirmala Makalingga Setyoko; Muhammad Ilham Alfarizi (Yayasan Education and Social Center, 2022)
For most people, snacks are one of the things that must be available at home and at work. Whether it's, when doing activities or relaxing, light snacks can always be the perfect companion to make the mood more elevated and also increase productivity. Among the wide variety of snacks to choose from, chips remain a favorite for some. With a crunchy texture and practical for consumption, chips seem to be unable to miss attention when choosing snacks to be used as stock at home. The flavor variants of chips are also diverse so that they are easier to adjust to taste, some are savory, salty, and also spicy. There is also a variant of chips with a sweet taste that is not only addictive, namely banana chips (Banana Chips). Banana chips are very suitable as a snack that is able to pamper the tongue, as well as meet the needs of important nutrients in the body. Banana Fruit Itself has about 136 calories for every 100 grams which overall comes from carbohydrates that have health and nutritional benefits, so it needs to be spread in the community. This community service program aims to provide solutions to problems that exist in Gunungsari village specifically for banana chip producers, namely the lack of quality of goods sold and produced in the area. Therefore, coaching program activities are carried out starting from increasing the understanding of the target community related to the processing of bananas into various innovative products, as well as providing knowledge of the benefits of bananas from nutritional and health aspects